Innovation in Inspection Planning Using The Corrosion Assessment Information System (CAIS) Analytical Tool to Prevent Stationary Equipment Failure in Crude Distillation Unit (CDU) - Muki Satya Permana; Mirwan Prasetiyo Soeweify; Brammantyo Nugroho; Fauzi Yusupandi; Hary Devianto; Ardian Dwi Prakoso (Scientific Contributions Oil and Gas, 2025)
Equipment failure caused by corrosion remains a critical challenge in ensuring the reliability and refinery asset integrity in the oil and gas industry. This study aims to develop a Corrosion Assessment Information System (CAIS), designed to assess and visualize corrosion severity through a color-coded Process Flow Diagram (PFD). The CAIS methodology consists of four key stages: analysis of design and operational data, process simulation and validation, compilation of contaminant data for each Crude Distillation Unit (CDU), and identification of corrosion mechanisms according to API 581 and API 571 standards. The system produces a corrosion risk map with four color indicators i.e. green (low), blue (moderate), yellow (high), and red (very high) which assists in prioritizing inspection and maintenance activities based on corrosion severity. Implementation results demonstrate that CAIS improves analytical efficiency, data accessibility, and collaboration between engineering and maintenance teams. Furthermore, it supports predictive monitoring and enables faster decision-making to reduce corrosion-related failures. External validation and integration into refinery workflows confirm CAIS as a strategic digital solution that strengthens risk-based inspection and predictive maintenance practices. Overall, CAIS provides a reliable platform for enhancing digital corrosion monitoring and asset integrity management at PT Kilang Pertamina Internasional, Refinery Unit VI Balongan, Indonesia.